2002
DOI: 10.1074/jbc.m101089200
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of NF-κB for Chromium(VI)-induced Cytotoxicity Is Revealed by Expression of IκB Kinase-β Mutant

Abstract: A wide range of signals, many of which are thought to be related to cellular stress, induce expression of early response genes through the NF-B family of transcription factors (1-4). In resting cells, NF-B is retained in cytoplasm in its inactive form by interaction with one of a number of inhibitory molecules including IB␣, IB␤, IB⑀, p105, and p100. Activation of the NF-B signaling cascade results in a complete degradation of IB or carboxyl-terminal partial degradation of the p105 and p100 precursors, allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Cr(VI) has been shown to both inhibit and activate the transcriptional activity of NF-(B [71,72], which may be related to differences in Cr concentration and cell type [73]. In the present study, Cr-induced upregulation of these oncogenes was observed in the normal BJ-hTERT cells, but abrogated in the B-5Cr cells.…”
Section: Discussionsupporting
confidence: 45%
“…Cr(VI) has been shown to both inhibit and activate the transcriptional activity of NF-(B [71,72], which may be related to differences in Cr concentration and cell type [73]. In the present study, Cr-induced upregulation of these oncogenes was observed in the normal BJ-hTERT cells, but abrogated in the B-5Cr cells.…”
Section: Discussionsupporting
confidence: 45%
“…Such Cr(VI)-induced cell death could be partially inhibited by expression of exogenous cIAP1, an inhibitor of caspases, indicating noncaspase cytotoxic mechanisms may be involved in Cr(VI)-induced cell death. Indeed, combination of cIAP1 and the antioxidant N-acetylcysteine resulted in a significant inhibition of Cr(VI)-induced cell death of NF-κB-inhibited cells (53). These results suggest that NF-κB is essential for inhibiting ROS-dependent cytotoxicity.…”
Section: Chromium(vi)mentioning
confidence: 79%
“…Cr(VI) is able to activate NF-κB at lower concentrations (<50 µM) in T cells (51), macrophages (52), bronchial epithelial cells (53), and human breast cancer cells (29). The final concentration of Cr(VI) is critical for this metal to induce or inhibit NF-κB.…”
Section: Chromium(vi)mentioning
confidence: 99%
“…To elucidate the signaling pathways leading to cyclin D1 induction by arsenite in human HaCat cells, we investigated the potential role of NF-nB in the cyclin D1 induction by arsenite, because it is believed that NF-nB transactivation is associated with arsenite-induced tumor promotion (47). NF-nB is bound to an inhibitory protein, InBa in an inactive form in most cells, and composed of NF-nB p50 and Rel A p65 subunits (48). In response to stress, cytokine, or growth factor, InBa is phosphorylated by IKKa/ h and then ubiquitinated and degraded by the proteasome, enabling nuclear translocation and binding of p50/p65 to the promoter region of target genes (49).…”
Section: Cell Cycle Progression Induced By Arsenite In Hacat Cellsmentioning
confidence: 99%